Implementasi Metode Marr-Hilderth Operator Untuk Mendeteksi Batas Tepi Pantai - Sitorus, Merida Christina (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2022)
Changes in the shape of the waterfront greatly impact the tourism business, which causes a reduction in domestic and foreign visitors to visit. One way to make it easier to obtain information about changes in the shoreline is to utilize the information contained in a coastal image. Edge detection is the first step of image segmentation to obtain information in an image. The edge contains from points that have a difference with the others. This study describes how to apply the Marr-Hilderth Operator method to detect image edges. Edge detection is the initial process to obtain information in images and characterize object boundaries, then edges can be used in the process of segmentation and identification of objects in images. The benefit of the detection of coastal boundaries is carried out to provide information to tourist area entrepreneurs regarding changes in the shape of the beach, so that the effects can be minimized as early as possible and make it easier for tourism object managers to obtain information about changes in the shape of the beach.